CONSERVATION AND THE EVOLUTIONS OF A SOCIETY, THE EXAMPLE OF GHADAMES, LIBYA - Damiani, Yann; Paccoud, Grégoire (Memorias del Seminario Iberoamericano de Arquitectura y Construcción con Tierra - SIACOT, 2010)
The present paper intends to address Ghadames Old Town (Libya), world heritage property since 1986. It is based on the conservation and valorisation program undertaken by CRAterre with the local authorities between 2007 and 2009. Thus, several training sessions, building projects and logistic activities were undertaken during 2 years. One the critical activities in this isolated city was the installation of a large brickyard so as to produce enough adobes for the large conservation project. The description of the steps and conditions to implement this brickyard is the starting point of the paper. The analysis of the evolutions of this specific activity from traditional to semi-industrial practices, leads to the issue of conservation in a quickly evolving society. The research of the causes of these changes questions the impact of political, economical and cultural changes on the conservation policies in Ghadames. Starting from the evolution of adobe brick production in Ghadames, this very theoretical question is enriched with answers from the field and is turned towards the recurring issue of the adaptation of earthen heritage to contemporary uses. However, the content of this paper concentrates on the experience of Ghadames.